2021
DOI: 10.21203/rs.3.rs-582026/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Effect of Sodium-Glucose Cotransporter 2 (SGLT2) Inhibitors on Left Ventricular Remodelling and Longitudinal Strain: A Prospective Observational Study

Abstract: Background: Sodium-glucose cotransporter 2 inhibitors (SGLT2i) lower cardiovascular events in type 2 diabetes mellitus (T2DM) patients, although the mechanisms underlying these benefits are not clearly understood. Our aim was to study the effects of SGLT2i on left ventricular remodelling and longitudinal strain.Methods: Between November 2019 and April 2020, we included 52 patients with T2DM ≥18 years old, with HbA1c between 6.5% and 10.0%, and estimated glomerular filtration ≥45 ml/min/1.73 m2. Patients were c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 0 publications
1
4
0
Order By: Relevance
“…is study is not aimed at patients with STEMI, though Gamaza-Chulián et al [22] confirmed the protective effect of SGLT2i on ventricular remodeling through a prospective cohort study. In this study, the subjects were patients with anterior wall STEMI, which were more targeted.…”
Section: Myocardial Interstitial Fibrosis Cardiomyocyte Inflammation ...mentioning
confidence: 99%
“…is study is not aimed at patients with STEMI, though Gamaza-Chulián et al [22] confirmed the protective effect of SGLT2i on ventricular remodeling through a prospective cohort study. In this study, the subjects were patients with anterior wall STEMI, which were more targeted.…”
Section: Myocardial Interstitial Fibrosis Cardiomyocyte Inflammation ...mentioning
confidence: 99%
“…78 In the clinical trial of S. Gamaza-Chulian et al in 52 patients with type 2 diabetes mellitus and without CHF a 6-month treatment with various SGLT2i was associated with a significant increase in GLS by a mean 1.29 ± 0.47 (p = 0.011) in comparison to the control group, where GLS increased by 0.40 ± 0.62 (p = 0.34). 79 Similar data were obtained in 53 diabetic patients with CHF with reduced, mildly reduced and preserved EF: the GLS significantly increased after 6 months of dapagliflozin therapy, moreover this positive effect was more pronounced in patients with preserved EF. 80 1.3 | Speckle tracking analysis utility in patients with heart failure with reduced EF treatment…”
Section: Speckle Tracking Analysis Utility In Heart Failure With Pres...supporting
confidence: 73%
“…The protective effect of SGLT2i on LV systolic function in non‐diabetic mice treated with doxorubicin has been demonstrated in an experimental study, where empagliflozin prevented the reduction of global radial and longitudinal strain 78 . In the clinical trial of S. Gamaza‐Chulian et al in 52 patients with type 2 diabetes mellitus and without CHF a 6‐month treatment with various SGLT2i was associated with a significant increase in GLS by a mean 1.29 ± 0.47 ( p = 0.011) in comparison to the control group, where GLS increased by 0.40 ± 0.62 ( p = 0.34) 79 . Similar data were obtained in 53 diabetic patients with CHF with reduced, mildly reduced and preserved EF: the GLS significantly increased after 6 months of dapagliflozin therapy, moreover this positive effect was more pronounced in patients with preserved EF 80 …”
Section: Introductionmentioning
confidence: 98%
“…In the present study, it was shown that Empagliflozin could improve global longitudinal contraction with its positive effects on the increased RAA system and impaired substrate metabolism. The study of Chulian et al., with fewer cases, supports the fact that SGLT‐2 inhibitors increase GLS 20 …”
Section: Discussionmentioning
confidence: 82%
“…The study of Chulian et al, with fewer cases, supports the fact that SGLT-2 inhibitors increase GLS. 20 Cardiac metabolism depends on aerobic oxidation. The continuous energy provided by this oxidation, creates MME activity along with left ventricular structure and function.…”
Section: Discussionmentioning
confidence: 99%